Childhood psychological abuse and relational aggression among adolescents: A moderated chain mediation model - Li, Ting; Huang, Yuhuai; Jiang, Meiru; Ma, Shutao; Ma, Yankun (Frontiers in Psychology, 2023)
To investigate the influence of childhood psychological abuse on relational aggression among middle school students and its internal mechanism, a cluster sampling survey was administered to 1,868 middle school students. The results demonstrated that: (1) childhood psychological abuse was significantly positively related to relational aggression; (2) childhood psychological abuse was significantly linked with adolescents' relational aggression through the separate mediating effects of rejection sensitivity and relational victimization, as well as through the chain mediating effects of rejection sensitivity and relational victimization; (3) the chain mediated effect of childhood psychological abuse on relational aggression through rejection sensitivity and relational victimization was moderated by cognitive reappraisal. This study is helpful to demonstrate the protective effect of cognitive reappraisal and reveal the internal mechanism of childhood psychological abuse on relational aggression.